Hambatan Adaptasi Mata Pencarian Kelompok Rentan Dalam Relokasi Masyarakat Pesisir KEK Mandalika - Rani, Anisa Puspa; Nurjannah, Siti; Hamdi, Saipul; Chaniago, Dwi Setiawan; Salsabila, Sally (Prodi Sosiologi Universitas Mataram, 2024)
Vulnerable groups at the margins of development are often the most affected in the development process. The development of the Mandalika area as a new tourism center exposes vulnerable groups to situations that require them to be able to adapt to the development of tourism economic activities in the region. This study aims to examine the obstacles to livelihood adaptation of vulnerable groups in relocation due to the development of the Mandalika Tourism Area. This research is case study research with a qualitative approach. Theoretically, in one spectrum, this research uses a political economy perspective as an alternative in understanding the dynamics of vulnerable groups of coastal communities who are relocated due to the infiltration of ongoing tourism development in the Mandalika Special Economic Zone. This research found a number of obstacles in the process of adapting the livelihoods of vulnerable groups, namely related to the protracted relocation process, the economic value in land and settlement compensation is small, relocation is oriented towards resettlement rather than socio-economic recovery of the community and the characteristics of jobs available in the area have not favored the needs of vulnerable groups. This research sees that there are differences in the pace of economic development and social development where state intervention in supporting regional operations is still concentrated on infrastructure development in stimulating business activities for the needs of the tourism economy. Meanwhile, social development, especially interventions to support economic recovery and adapt the livelihoods of vulnerable groups, has not yet become the main discourse in supporting the economic transformation of local communities.